Pregnant Women's Perception and Attitude Towards Mode of Delivery in Erbil City- A Qualitative Study - Khadija Mirkhan Ahmed; Tiran Jamil Piro (Hawler Medical University, 2022)
Background and objective: The childbirth experience has always been represented as a significant event in women's lives. With the rising rates of cesarean sections in the Kurdi-stan region and lack of evidence, this study was conducted to explore women's perceptions and attitudes towards a mode of delivery. Method: An exploratory qualitative design with indepth interviews was used to collect data from 18 pregnant women. All in-depth interviews were tape-recorded, transcribed, and subsequently analyzed. Inductive content analysis methods were used to establish the meaning units, subthemes, and main themes. Result: From the analysis of depth-interview data of 18 pregnant women, 48 meaning units were obtained. These meaning units were collected into four themes and nine sub-themes. These themes were identified as perceived advantages and disadvantages of a mode of delivery, knowledge deficit, weak healthcare provider's role, and fear related to vaginal delivery. Conclusion: Results showed that women's decision-making on the mode of delivery depended on their family and friends' opinions. Health care providers had few roles in providing the necessary information about the advantages and disadvantages of delivery modes, childbirth, and decreasing their fear of vaginal delivery.